EARTH’S MAGNETIC FIELD DYNAMICS: SPACE WEATHER AND SOLAR CYCLE EFFECT EXHIBITING - Sukharev, A. L.; Sobitnyak, L. I.; Ryabov, M. I.; Orlyuk, M. I.; Orliuk, I. M.; Romenets, A. A. (Одеські астрономічні публікації, 2014)
According to the “Odessa” and “Kiev” observatories total vector magnetic field variations data for 2008-2010 period, dynamics of the space weather manifestations were considered. Wavelet analysis application made the determination of structure changing in circadian period possible. The features of displaying 12, 8 and 6 hour periods are shown. The nature of their correlation and modulation in solar and geomagnetic activity changing is seen. Two stations changes differences that can result from the latitudinal dependence are examined. The existence of “Odessa” magnetic anomaly located on land and at sea is reviewed